Abnormal visual phenomena in posterior cortical atrophy. - Crutch, S; Lehmann, M; Gorgoraptis, N; Kaski, D; Ryan, N; Husain, M; Warrington, E (2011)
Individuals with posterior cortical atrophy (PCA) report a host of unusual and poorly explained visual disturbances. This preliminary report describes a single patient (CRO), and documents and investigates abnormally prolonged colour afterimages (concurrent and prolonged perception of colours complimentary to the colour of an observed stimulus), perceived motion of static stimuli, and better reading of small than large letters. We also evaluate CRO's visual and vestibular functions in an effort to understand the origin of her experience of room tilt illusion, a disturbing phenomenon not previously observed in individuals with cortical degenerative disease. These visual symptoms are set in the context of a 4-year longitudinal neuropsychological and neuroimaging investigation of CRO's visual and other cognitive skills. We hypothesise that prolonged colour after-images are attributable to relative sparing of V1 inhibitory interneurons; perceived motion of static stimuli reflects weak magnocellular function; better reading of small than large letters indicates a reduced effective field of vision; and room tilt illusion effects are caused by disordered integration of visual and vestibular information. This study contributes to the growing characterisation of PCA whose atypical early visual symptoms are often heterogeneous and frequently under-recognised.